Effect Of Profitabilitas, Liquidity, Laverage & Inventory Turnover On The Devisiation Of The Actual Growth Rate From Sustainable Growth Rate In Consumer Non Cylical Companies - Mohamad Zulman Hakim; Anggi Novianti; Wati Yaramah; Triana Zuhrotun Aulia; Hutsna Dara Sarra; Eni Suharti (Cita konsultindo, 2023)
The purpose of this study was to determine the effect of return on assets, current ratio, debt to equity ratio and inventory turnover, on the deviation of the actual growth rate from the sustainable growth rate in non-cyclical consumer companies listed on the Indonesia Stock Exchange (IDX). The research period is 4 years, namely the period 2018 - 2021. The sampling technique uses a purposive sampling technique. The criteria set as 32 companies. The type of data used is secondary data obtained from the Indonesia Stock Exchange. The analytical method used is panel data regression analysis. The results showed that inventory turnover had a positive effect on the deviation of the actual growth rate from the sustainable growth rate, while the return on assets, the current ratio and debt to equity ratio were not significant for the deviation of the actual growth rate from the sustainable growth rate. The stages of data analysis carried out in this study used the eviews version 10 application program.